2009
DOI: 10.1002/gps.2291
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an association of the big five personality factors with recurrence of depressive symptoms in later life

Abstract: SUMMARYObjectives Although it is well known that recurrence of late-life depression is very common, little is known about the characteristics of older people who are vulnerable for recurrence. In order to identify characteristics of those who are at risk, the present study aimed to investigate the strength of the associations of the big five personality factors with recurrence in later life. Secondly, we studied whether there are gender and age differences in the strength of these associations. Methods Using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 45 publications
(49 reference statements)
1
36
0
2
Order By: Relevance
“…35 BPD increases the risk of MDE recurrence, 44 and aging alone does not seem to affect the strength of the relationship between personality disorders and depression. 45 Under stressful situations, temperamental traits might be considered a risk factor for developing episodes of major depression in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…35 BPD increases the risk of MDE recurrence, 44 and aging alone does not seem to affect the strength of the relationship between personality disorders and depression. 45 Under stressful situations, temperamental traits might be considered a risk factor for developing episodes of major depression in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In samples of children it has also been shown that there is a positive association between depression and neuroticism, as well as a negative association between depression and conscientiousness, extraversion, openness and agreeableness (Carrasco and del Barrio, 2007). It has also been found that higher scores on neuroticism are associated with a higher recurrence of depressive episodes in older adults (Steunenberg, Braam, Beekman, Deeg, and Kerkhof, 2009). …”
Section: Personality and Psychological Healthmentioning
confidence: 98%
“…The anxious distress specifier is assumed to identify a more severe form of depression and can be assumed to have considerable overlap with the major depressive disorder with comorbid PD, since somatic anxiety symptoms are the core symptoms of PD. Therefore, we may not be looking at "pure" comorbidity, but merely a heterogeneous group where some have a comorbid PD and some have an anxious depression as a specific subtype of depression (van der Veen et al, 2014).…”
Section: Determinantsmentioning
confidence: 99%
“…Nonetheless, the literature on "anxiety in depression" is difficult to interpret as studies on depressed patients with a high level of anxiety symptoms and depressed patients with concurrent anxiety disorders are often grouped together. Recently, we have shown that, in a sample of patients with depression, comorbid anxious distress or as comorbid anxiety disorders, identify completely different patients, where, for example, depressed older persons who report high levels of (somatic) anxiety symptoms are of a different group than patients suffering from comorbid PD (van der Veen et al, 2014). Determinants of anxious distress and of comorbid anxiety disorders should therefore be examined separately.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation